Conflitos e organização do espaço público em processo de tomada de decisão na França e no Brasil: a negociação em áreas protegidas - Véronique Van Tilbeurgh; Guilherme Borges da Costa (Confins)
The objective of this article is to question the link between conflict and public space organization in the negotiation process of a public decision. We compare the negotiations in two protected areas ; Marine Park in the Iroise Sea (in France) and the Protected Area Várzea do Tietê River (in Brazil). This comparison shows that in both cases, the decision to be negotiated was imposed by one party, but this situation has an amplifying effect of the conflict in France. The explanations for these variations refer to the forms of organization of public space in these two countries.